Filsafat Ilmu dalam Perkembangan Ilmu Manajemen Rantai Pasok - Nugraheni, Diyah Dwi; Sutopo, Wahyudi (Metris: Jurnal Sains dan Teknologi, 2016)
Philosophy plays an important role in any development of science. Besides philosophy, science also an important thing to understand. Philosophy and science are related to each other. Science philosophy defined as a philosophical review that examined about the nature of science, including the science of supply chain management. This study was conducted by literature study then conducted an analysis based on the evolution, development of science, terminology, and contribution of supply chain management. The evolution of supply chain management consists of the creation era, integration era, globalization era, specialization era and SCM 2.0. The development of supply chain management science began in the 1950s, which in that year is considered in terms of military logistics. Until in the end the term "supply chain management" appeared in 1997. Terminology supply chain management consists of collaboration, integration and sustainability of the supply chain. Contribution to the implementation of supply chain management is to achieve customer satisfaction, increase revenues, decrease costs, higher asset utilization, increase profits, and the greater company. This study resulted in the mapping of supply chain management science so that easy to learn.